Urinary incontinence and sabulous cystitis in mares: report of five cases - de Melo, Ubiratan Pereira; Ferreira, Cintia (Brazilian Journal of Veterinary Medicine, 2024)
This report describes five cases of urinary incontinence in Quarter Horse mares associated with the development of sabulous cystitis. The animals in this study had a history of persistent urinary incontinence for eight months, with clinical signs of continuous dribbling urine during rest and movement. The initial treatment with antibiotics and anti-inflammatory drugs was ineffective. Clinical examination revealed severe scalding in the perineal region and on the medial aspect of the hind limbs, along with neurological signs such as ataxia, hind limb paresis, and diminished perineal reflexes. Transrectal ultrasonography confirmed bladder distension and the presence of hyperechoic particles in the urine. Urinalysis revealed typical features of sabulous cystitis, including abundant calcium carbonate crystals. Despite treatment with corticosteroids, antibiotics, and daily bladder lavage with physiological saline, no substantial clinical improvement was observed. The limited therapeutic response and guarded prognosis were discussed with the owner, who opted to monitor the mares without altering their clinical condition for two years. This report highlights the complexity of managing urinary incontinence associated with sabulous cystitis in horses and emphasizes the importance of accurate diagnosis and early recognition of clinical signs for effective treatment.